PRESENTATION - López de Castro , Sandra (Revista Arbitrada Formación Gerencial, 2024)
The peer-reviewed journal Formación Gerencial is pleased to present the second issue of the 23rd year of the journal, corresponding to November 2024. From the Journal, we want to become a support to active researchers, contributing to the publication and dissemination of their research and the contributions they make to the solution of social problems and the construction of theories that contribute to the advancement of managerial and humanistic sciences.